Pengaruh Budaya Organisasi Terhadap Manajemen Stres Dan Kesejahteraan Mental Karyawan Generasi Milenial - Yesi Novita Sari; Vanessa Zahra; Merika Setiawati (CV. ITTC INDONESIA, 2025)
Organizational culture plays a strategic role in shaping employee behavior, attitudes, and psychological well-being, particularly among millennial employees who currently dominate the workforce. Millennials are characterized by dynamic work styles, a strong orientation toward meaningful work, and sensitivity to supportive work environments. This study aims to analyze the influence of organizational culture on stress management and mental well-being of millennial employees. The research method employed is a systematic literature review of management and organizational psychology textbooks, as well as relevant national and international journal articles. The findings indicate that a positive, participative, and supportive organizational culture significantly reduces work-related stress and enhances the mental well-being of millennial employees. Cultures emphasizing open communication, organizational justice, and work-life balance foster healthier mental work environments. Therefore, organizations are encouraged to develop adaptive and human-centered cultures to support sustainable stress management and mental well-being among millennial employees.